Pengaruh Digital Marketing dan Citra Produk Lokal Terhadap Keputusan Pembelian Konsumen Pada Bubuk Kopi Lampu Gantung Melaluibrand Awareness Sebagai Variabel Intervening - Rayhan Rugasa (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of digital marketing and local product image on consumer purchasing decisions through brand awareness as an intervening variable for Lampu Gantung Coffee Powder in Solok Regency. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 96 respondents who are consumers of Lampu Gantung Coffee Powder. The sampling technique used in this study was purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. Descriptive analysis was applied to describe the research variables through the calculation of the Respondent Achievement Level (TCR). The results indicate that digital marketing and local product image have a positive and significant effect on brand awareness. Furthermore, brand awareness has a positive and significant effect on purchasing decisions. The findings also reveal that brand awareness mediates the relationship between digital marketing and local product image on purchasing decisions. This study is expected to provide practical insights for local businesses in developing effective digital marketing strategies and strengthening local product image to enhance brand awareness and consumer purchasing decisions